1999
DOI: 10.1007/s007750050320
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical characterization of a novel precursor for covalently bound macromolecular MRI contrast agents

Abstract: The ligand DOTASA was designed and synthesized in the aim of obtaining a kinetically and thermodynamically stable Gd(III) chelate which, through its uncoordinated carboxylate function, will provide an efficient pathway to couple the complex to bio- or macromolecules without affecting the coordination pattern of DOTA. Furthermore, it allows us to study the influence of an extra carboxylate arm on the parameters determining proton relaxivity in comparison to the commercial agent [Gd(DOTA)(H2O)]-. A combined vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…[19] A similar effect was observed upon substitution of one carboxylate of DOTA 4-or DTPA 5-by noncharged amide groups. In both systems, the water exchange rate diminished by a factor of 3-4.…”
Section: O Nmr and Epr Measurementssupporting
confidence: 62%
“…[19] A similar effect was observed upon substitution of one carboxylate of DOTA 4-or DTPA 5-by noncharged amide groups. In both systems, the water exchange rate diminished by a factor of 3-4.…”
Section: O Nmr and Epr Measurementssupporting
confidence: 62%
“…Synthesis of NaH[Gd(DOTASA)´H 2 O]: The ligand DOTASA was synthesized according to a procedure published elsewhere [11] (H 5 DOTASA 1,4,7,10-tetraazacyclododecane-1-succinic-4,7,10-triacetic acid). The NaH[Gd(DOTASA)´H 2 275 mg, 7.2 Â 10 À4 mol, 3 equiv] were incubated for 10 minutes (the pH was checked with pH paper and it showed to be 7 ± 8) prior to the addition of Nmethyldodecylamine (180 mL; 7.2 Â 10 À4 mol, 3 equiv; Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…Since the micelles formed are expected to have slow rotation, the treatment we use also includes non-extreme narrowing conditions. The dipolar contribution is given by Equations (11). [37] The quadrupolar contributions is given by Equation (12).…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] In order to enhance r 1 , it has been found that: 1) tumbling has to be slowed down by attaching the chelate to macromolecular assemblies, such as proteins, [2,3] dendrimers, [4,5] micellar aggregates [6,7] or polymers; [8] 2) the water-exchange rate has to be increased by promotion of the departure of a coordinated water molecule; this is achieved by the design of optimized chelates such as Gd III complexes of TRITA (1,4,7,10-tetraazacyclotridecane-1,4,7,10-tetraacetic acid), [9] EPTPA (ethylenepropylenetriaminepentaacetic Abstract: We report the study of binuclear Ln III chelates of OHEC (OHEC = octaazacyclohexacosane-1, 4,7,10,14,17,20,23-octaacetate). The interconversion between two isomeric forms, which occurs in aqueous solution, has been studied by NMR, UV/ Vis, EPR, and luminescence spectroscopy, as well as by classical molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%